Implementasi Algoritma Jump Point Search Pada Game Prince Of Walangsungsang - Rio Andriyat Krisdiawan; Heru Budianto; fitra imaniar (Teknik Informatika Universitas Suryakancana Cianjur, 2023)
The development of the gaming industry has provided an opportunity to combine entertainment with education. In this context, this study aims to implement the Jump Point Search (JPS) algorithm in the game